Nexus between Working Capital Management and the Profitability: An Empirical Analysis - Ayoungman, Fairtown Zhou; Tanchangya, Papel (The journal of contemporary issues in business and government, 2021)
The net profit of any organization for a certain time period can be explained as the final outcome of it investing, financing and operating activities. All of these activities are greatly influenced by management’s decision and a number of other internal and external environmental factors. Working Capital Management is widely usedto evaluate and measure the risks and returns of a company. The research is specifically concerned about studying the impact of working capital management on the profitability of textile sector listed companies in Karachi Stock Exchange. The study takes Return on Asset as dependent variable and as a measure of profitability. Average payment period, Average Collection Period, Average Inventory Days in Hand, Cash Ratio, Quick Ratio and Current Ratio are as considered as independent variables. The research is based on 5 year financial statement data ranging from 2017 to 2021. The results for the research were mixed i.e. both significant and insignificant correlation was found between independent and dependent variables.